2011
DOI: 10.1017/s0033291711001991
|View full text |Cite
|
Sign up to set email alerts
|

The influence of gender on clinical and social characteristics of patients at psychosis onset: a report from the Psychosis Incident Cohort Outcome Study (PICOS)

Abstract: BACKGROUND. This paper examined the hypothesis that males with first-episode psychosis (FEP) experience lower pre-morbid adjustment, greater social disability and more self-perceived needs at illness onset than females(by controlling for duration of untreated psychosis, diagnosis, age and symptoms at onset). Results disconfirming this hypothesis were thought to suggest the potentially mediating role of social context in determining the impact of symptoms and disability on the everyday lives of male patients in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
44
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(50 citation statements)
references
References 62 publications
(80 reference statements)
6
44
0
Order By: Relevance
“…No statistically significant differences by gender were seen in symptoms at presentation as assessed on the Positive and Negative Syndrome Scale (Kay et al, 1987). However, males reported greater pre-morbid functioning and higher social disability at illness onset, but fewer unmet needs in the functioning domain than females did (Bertani et al, 2012). No study has investigated sex differences in Italian samples of UHR patients so far.…”
Section: Changes In Services Organization and Sex Differences In Clinmentioning
confidence: 93%
See 2 more Smart Citations
“…No statistically significant differences by gender were seen in symptoms at presentation as assessed on the Positive and Negative Syndrome Scale (Kay et al, 1987). However, males reported greater pre-morbid functioning and higher social disability at illness onset, but fewer unmet needs in the functioning domain than females did (Bertani et al, 2012). No study has investigated sex differences in Italian samples of UHR patients so far.…”
Section: Changes In Services Organization and Sex Differences In Clinmentioning
confidence: 93%
“…Bertani et al (2012) analyzed a large epidemiologically representative cohort of first episode of psychosis (FEP) patients (n ¼517) who were assessed within a multi-site research project examining incident cases of psychosis in the Veneto region of Italy, and found that males were nearly 3 years younger and had longer DUP than female patients. No statistically significant differences by gender were seen in symptoms at presentation as assessed on the Positive and Negative Syndrome Scale (Kay et al, 1987).…”
Section: Changes In Services Organization and Sex Differences In Clinmentioning
confidence: 99%
See 1 more Smart Citation
“…This cross-sectional study was conducted within the framework of the Psychosis Incident Cohort Outcome Study (PICOS), a multisite collaborative study that examined the relative roles of clinical, social, genetic, and morpho-functional factors in predicting outcomes among patients experiencing a first episode of psychosis who were in contact with public mental health services in the Veneto Region, northeast Italy (22,26). This study assessed experiences of discrimination in a sample of first-episode patients recruited from a subset of sites (30%) participating in PICOS; sites were selected on the basis of availability of local resources to perform these evaluations.…”
Section: Methodsmentioning
confidence: 99%
“…In fact, the literature reports a substantial difference between the clinical and social needs of this group and those of patients with illnesses of longer duration. The former are generally young, living with their families, attending educational or training systems, and seeking to enter the labor market (21,22). Patients experiencing a first episode of psychosis may therefore report more discrimination in life domains pertaining to young people's social world (such as training or education, friendship, and family relations), but empirical data are lacking.…”
mentioning
confidence: 99%